The effect of kick-box on violence tendency of the high school students - AYSEGUL SARIKAYA; AYSE ALPTEKIN (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This study aims to compare the violent tendencies of High School students who participate in kickboxing with those of students who do not.Method: In total, 103 licensed kickboxers from Konya were surveyed, including 18 women and 85 men. The sample was selected using a stratified sampling technique. Data analysis was performed using SPSS and LISREL. The statistical "Independent Sampling t-Test" was used to analyze the disparity between the two groups. Confirmatory Factor Analysis was used to ensure the reliability of your scale in this study.Findings: The compliance indices are within reasonable ranges, as shown by the CFA results; this suggests that the scale was adequate for the purposes of the study. Finding a Cronbach’s alpha of.66 indicates that the scale is a credible research tool for this study. The study found that compared to non-kickboxer secondary school students, kickboxer secondary school students had lower violent tendencies.Implications/Novel Contribution: Kickboxing, which incorporates a wide variety of martial arts techniques, has not been the subject of any research on violence in young people. Therefore, this research is expected to add new insight to the existing literature on kickboxing’s impact on young people’s aggressive behavior.